Business law and its effects on commercial transactions - Isretno Israhadi, Evita (Opción, 2019)
This study surveyed the Indonesian business law, import and joint venture licensing regulations and found out how the law has implemented sweeping regulations imposing non-automatic import licensing procedures. The study adopted a qualitative method approach employing the inductive method of collecting data. As a result, the Indonesian business law even violated the WTO agreement by introducing arbitrary regulations sanctioning imports in a few cases. In conclusion, the government must also try to accelerate regulatory reforms, particularly in services sectors where market restrictions have been shown to negatively affect trade in manufactured goods.